Effect of precipitation hardening heat treatment on mechanical and microstructure features of dissimilar friction stir welded AA2024-T6 and AA6061-T6 alloys. (January 2018) - Pabandi, Hossein Karami; Jashnani, Hamid Reza; Paidar, Moslem
Abstract: The friction stir welding of AA2024-T6 to AA6061-T6 plates with a 4 mm thickness has been studied at constant traverse and rotational speeds of 1000 rpm and 100 mm/min, respectively. The position of alloys and the effects of precipitation hardening heat treatment in retreating and advancing side in the friction stir welding were analyzed. The tool with taper threaded pin was used for welding. Macro and microstructural analysis were investigated by using Optical and Field Emission-Scanning Electron Microscopes (FE-SEM) to check out the welded joints. Micro-hardness and Tensile tests were also done to study mechanical attributes of the joints. Microstructural analysis revealed some grain coarsening in the weld zones and base metals after heat treatment. The results also showed that mixing between the two alloys and their tensile strength improved when AA6061 alloy was placed on the advancing part. Furthermore, the ultimate tensile strength of the heat treated welds was higher than non-heat treated welds which can be attributed to increasing of strength and hardness of weld zones, especially HAZ. Besides, the fracture area of the welded joints shifted from the HAZ of AA6061 to the SZ which confirms significant role of precipitation hardening heat treatment on the mechanical effects of the welded joints. In the SEM images of the fracture surface, precipitated Mg2 Si particles in HAZ were observed.